Informed heart. Middlesex - "Bettelheim, Bruno" (England, 1986)
We are in great haste to send and receive messages from outer space. But so hectic and often so tedious are our days, that many of us have nothing of importance to communicate to those close to us. Never before have so many had it so good; no longer do we tremble in fear of sickness or hunger, of hidden evils in the dark, of the spell of witches. the burden of killing toil has been lifted from us, and machines, not the labor of our hands, will soon provide us with nearly all we need, and much that we don't really need. We have inherited freedoms man has striven after for centuries. Because of all this and much more we should be living in a dawn of great promise. But now that we are freer to enjoy life, we are deeply frustrated in our disappointments that the freedom and comfort, sought with such deep desire, do not give meaning and purpose to our lives.
Keywords: Psychology